2010
DOI: 10.1186/1471-2458-10-595
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between mild cognitive impairment and dietary pattern in chinese elderly? Results from a cross-sectional population study

Abstract: BackgroundDiet has an impact on cognitive function in most prior studies but its association with Mild Cognitive Impairment (MCI) in Chinese nonagenarians and centenarians has not been explored.Methods870 elder dujiangyan residents aged 90 years or more in 2005 census were investigated at community halls or at home. They underwent the Mini-Mental State Examination (MMSE) for assessment of cognitive function and replied to our questionnaire comprised of 12 food items and other risk factors. MCI was defined by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 18 publications
5
39
1
2
Order By: Relevance
“…[7][8]10] The main difference between the present study and the original analyses and report on the PLAD study was that the original report focused on minor cognitive impairment, and excluded the normal and the dementia group. [9] The present study found no statistically significant differences in terms of chronic bronchitis(P<0.001)between the two groups. It has been reported that no statistically significant association was found between the two groups in terms of chronic bronchitis after adjusting for independent variable factors (sex, age, education level and major occupation before 60 years of age).…”
Section: Discussioncontrasting
confidence: 66%
“…[7][8]10] The main difference between the present study and the original analyses and report on the PLAD study was that the original report focused on minor cognitive impairment, and excluded the normal and the dementia group. [9] The present study found no statistically significant differences in terms of chronic bronchitis(P<0.001)between the two groups. It has been reported that no statistically significant association was found between the two groups in terms of chronic bronchitis after adjusting for independent variable factors (sex, age, education level and major occupation before 60 years of age).…”
Section: Discussioncontrasting
confidence: 66%
“…The MMSE score level was set according to the fact that most participants in a previous PLAD study had no formal education. 9,18,20 The main difference between the present study and the original analyses and report on the PLAD study was that the original report focused on minor cognitive impairment, and excluded the normal and the dementia group. 18 The present study found no statistically significant differences in terms of food intake, nutritional content of each food item, frequency of consuming breakfast, main cooking methods or eating habits between the two groups, after adjusting for independent variable factors (sex, age, education level and major occupation before 60 years of age).…”
Section: Discussionmentioning
confidence: 82%
“…18 The study aimed to include all nonagenarians and centenarians in the area of Dujiangyan, although subjects with post-stroke related disease or Parkinson's disease, or who did not complete the MMSE test, were excluded. The study protocol was approved by the research Ethics Committee of Sichuan University.…”
Section: Study Population and Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Diet and nutrition have been studied as factors for promoting and maintaining health throughout life. 8 Dietary patterns have been associated with non-communicable chronic diseases, 9-13 mortality, [14][15][16] cognitive function, 17 obesity 10,12,[18][19] and the protective effect on being overweight. 14,18,[20][21] Unhealthy dietary patterns (sugar, fat, processed foods and refined grains) can be found in overweight younger adults 20,22 as well as in the elderly.…”
Section: Introductionmentioning
confidence: 99%